Energy saving potential and harmful extrass amount declines of the primary processing of oil - Yljev, L. M.; Melnikovska, L. O. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2011)
Extraction of stream information of setting was conducted, the chart of processing of oil is modeled by the program HYSYS, that allowed to get more exact information for calculations. Energy saving potential of setting of AVT A12/2 without a vacuum block and declines of amount of harmful extrass potential, was certain.